Siderite/PMS conditioning-pressurized vertical electro-osmotic dewatering process for activated sludge volume reduction: Evolution of protein secondary structure and typical amino acid in EPS. (1st August 2021) - Li, Enrui; Wang, Yili; Zhang, Daxin; Fan, Xiaoyang; Han, Zhibo; Yu, Fuling
Highlights: Siderite/PMS conditioning coupled with PEOD reduced 91.76% bound water in AS. Conditioning led to denser protein structure in TB-EPS and looser one in slime. Dewatering stages led to more water flow outsider of slime than TB-EPS. Ala / Lys-in slime and TB-EPS showed strong correlations with dewaterability. Siderite/PMS conditioning caused increased contacts between Ala-and water in slime. Abstract: In this study, the siderite/PMS conditioning-pressurized vertical electro-osmotic dewatering (PEOD) process was used to reduce the volume of activated sludge (AS). The changes in water content, cell, extracellular polymeric substances (EPS) distribution, protein secondary structures and typical amino acids in EPS fractions of AS along siderite/PMS conditioning-PEOD process were investigated. Results showed that the final water content (WC) of dewatered AS was 58.02% under the RSM optimized conditioning conditions of 0.05 g/g TSS siderite dosage, 0.23 g/g TSS PMS dosage, 600 kPa mechanical pressure and 20 V voltage. At conditioning and PEOD stages, the bound water content(BWC) of AS decreased by 25.23% and 91.76%, respectively. The HO and SO 4 − · generated from siderite activating PMS could lead to the disruption of cells. The ratio of Ala-to Lys (Ala/Lys) showed strong negative correlations with BWC or WC in slime ( R BWC 2 = − 0.803, p <0.01; R WC 2 = − 0.771, p <0.01) and TB-EPS ( R BWC 2 = − 0.693, p <0.01; R WC 2 = − 0.705, p <0.01), and could be considered as an indicator of AS dewaterability. Compared with raw AS, conditioning led to the occurrence of the denser protein structure in TB-EPS and the looser one in slime. The contact number between Ala-and water decreased in TB-EPS and increased in slime, which indicated that the migration of water adhered in TB-EPS to outer layer. At the DG, MC and EC process, while the looser protein structure in TB-EPS and the denser one in slime occurred, as well as higher contact number between Ala-and water in TB-EPS than that in slime, which indicated that more water flowed outsider of slime than TB-EPS. This implied that the variations of the compactness of protein secondary structures and the contact number between Ala-and water in EPS layers correlated with AS dewaterability. Graphical abstract: Image, graphical abstract